ChemInform Abstract: Synthesis of Ketones Through Microwave Irradiation Promoted Metal‐Free Alkylation of Aldehydes by Activation of C(sp3)—H Bond. Issue 10 (February 2016) - Zhang, Xinying; Wang, Zhangxin; Fan, Xuesen; Wang, Jianji
Abstract: This method for the preparation of ketones utilizes microwave irradiation promoted direct alkylation of aldehydes by activation of the inert C(sp 3 )‐H bond.